The Epidemiology and Outcomes of Percutaneous Coronary Intervention Before High‐Risk Noncardiac Surgery in Contemporary Practice: Insights From the Blue Cross Blue Shield of Michigan Cardiovascular Consortium (BMC2) Registry. Issue 3 (12th May 2014) - Muthappan, Palaniappan; Smith, Dean; Aronow, Herbert D.; Eagle, Kim; Wohns, David; Fox, James; Share, David; Gurm, Hitinder S.
Abstract : Background: Percutaneous coronary intervention (PCI) is sometimes performed with the intent to lower cardiovascular risk before high‐risk noncardiac surgery (HRNCS). There are limited data on the frequency and outcome of PCIs performed in this setting. Methods and Results: We assessed the frequency, characteristics, and in‐hospital outcomes of patients undergoing PCI as part of the preoperative workup for HRNCS among all 61 145 elective PCIs performed between 2002 and 2009 at 14 hospitals in the Blue Cross Blue Shield of Michigan Cardiovascular Consortium. Propensity matching was performed to compare outcomes of patients undergoing PCI before HRNCS with all other elective PCI patients. The frequency of PCI before HRNCS was low (4.2%). Patients undergoing PCI before HRNCS were older (67.3 versus 64.9 years, P <0.0001) and had a greater burden of comorbidity. Patients undergoing PCI before HRNCS had an increase in unadjusted major adverse cardiovascular events, postprocedure transfusion, contrast‐induced nephropathy, nephropathy requiring dialysis, and same‐admission coronary artery bypass graft surgery, but there was no difference in mortality (0.27% versus 0.14%, P =0.11). However, in propensity score–matched samples, there was a significant difference only in nephropathy requiring dialysis. Conclusions: The incidence of PCI performed in preparation for high‐risk noncardiac surgery is low, and these procedures are currently being performed on a highly selected high‐risk patient population.